Clear Cell Papillary Renal Cell Carcinoma in the Bilateral Native Kidneys after 2 Years of Renal Transplantation: Report of a Case and Review of the Literature. (30th June 2011) - Bing, Zhanyong; Tomaszewski, John E.
Abstract : Renal transplantation increases the probability of malignant tumors by about 2–4-fold overall with a much higher rate for renal epithelial malignancy. Renal tumors in renal transplant recipients are commonly conventional clear cell or papillary renal cell carcinoma. Clear cell papillary renal cell carcinoma is a recently described unique renal epithelial neoplasm with scant eosinophilic or moderate amount of clear cytoplasm and pyknotic small nuclei oriented commonly toward the apical surfaces. No such tumor has been reported in renal transplant recipients. In this paper, we describe a clear cell papillary renal cell carcinoma involving bilateral native kidneys in a patient who had received a renal transplant 2 years earlier. Clear cell papillary renal cell carcinoma commonly presents with low pathologic stage and lower Fuhrman grade and is clinically indolent. Additional cases are needed to evaluate the clinical behavior of this type of tumor in renal transplant recipients.